2019
DOI: 10.3390/photonics6030096
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Photonic-Crystal Surface-Emitting Lasers

Abstract: Photonic-crystal surface-emitting lasers (PCSELs) have attracted considerable attention as a novel semiconductor laser that surpasses traditional semiconductor lasers. In this review article, we review the current progress of PCSELs, including the demonstration of large-area coherent oscillation, the control of beam patterns, the demonstration of beam steering, and the realization of watt-class and high-beam-quality operation. Furthermore, we show very recent progress in the exploration of high brightness of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…For example, Kurosaka et al achieved on-chip beam-steering using photonic crystal band-edge lasers (Figure 3a). [35,36] The emission direction was controlled via the deformation of structural parameters, such as the air-hole shape and the lattice constant. The maximum beam steering angle was ± 30°, and the beam divergence angle was ≈1°.…”
Section: Photonic Crystal Lasermentioning
confidence: 99%
“…For example, Kurosaka et al achieved on-chip beam-steering using photonic crystal band-edge lasers (Figure 3a). [35,36] The emission direction was controlled via the deformation of structural parameters, such as the air-hole shape and the lattice constant. The maximum beam steering angle was ± 30°, and the beam divergence angle was ≈1°.…”
Section: Photonic Crystal Lasermentioning
confidence: 99%
“…[ 4 ] Both these approaches pose challenges to the epitaxial regrowth process, which needs to be optimized either for complete [ 4 ] or minimal [ 12–15 ] infilling of the etched holes defining the buried PC lattice. While most results on regrown PCSELs so far have been based on the GaAs material system for emission in the near‐infrared wavelength regime around 1 μm, there are a range of important application in the longer wavelength regime (1.2–1.6 μm), e.g., eye‐safe sources for laser imaging detection and ranging (Lidar), [ 16,17 ] free‐space optical communication, [ 18 ] or resonant pumps for erbium lasers, [ 19 ] that can be reached through the InP material system. Recently, McKenzie et al demonstrated the fabrication of 1550 nm PCSELs based on InP infilling of an InGaAsP grating layer, including lasing action from electrical pumping.…”
Section: Introductionmentioning
confidence: 99%
“…Additional applications for such surface emitting InP based devices include free-space communications [19], LiDAR, fibrebased sensing [1], etc.…”
mentioning
confidence: 99%
“…PCSEL devices have traditionally been realised with wafer fusion [2]- [5], but more recently epitaxial overgrowth through MBE [1] [20] and MOVPE has been utilised [21]- [24]. This move from wafer fusion to epitaxial regrowth has been critical for achieving high output powers [1] [9]. This is because the wafer fusion interface contains regions of discontinuous crystallinity, that result in undesirable defect states [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation